Witness Qualification and Quantification in Sexual Jarimah under Aceh Qanun: A Fiqh Jinayah Perspective on Mahkamah Syar’iyyah Banda Aceh Decisions - Aziz, Isfahani Azmil; Rohmah, Siti (International Journal of Business, Law, and Education, 2026)
This article examines the qualification and quantification of witness testimony in sexual jarimah adjudication under Aceh’s special criminal law regime, particularly Qanun Aceh No. 6 of 2014 on Jinayat and Qanun Aceh No. 7 of 2013 on Jinayat Procedure. The analysis focuses on zina, liwāṭ, musāḥaqah, khalwat and ikhtilāṭ through a normative-juridical and case-law reading of Mahkamah Syar’iyyah Banda Aceh decisions. The revised coding available in the manuscript covers fifteen decisions with complete witness-count data, while the broader corpus described by the author refers to sixteen decisions; the remaining decision should be completed before final submission. The findings show that most coded decisions did not satisfy the four-witness evidentiary threshold associated with zina in classical fiqh jinayah and in Article 182 of Qanun Aceh No. 7 of 2013. Judicial reasoning instead relied heavily on defendants’ confessions, corroborative witness statements, electronic evidence and physical indications. This evidentiary pattern raises a doctrinal tension between positive jinayat procedure, classical safeguards against qadhf, and contemporary due-process concerns, especially where co-defendants or alleged participants function as “crown witnesses” while simultaneously occupying the position of maqdhūf ʿalayh. The article argues that Aceh’s jinayat evidentiary framework requires doctrinal clarification and regulatory harmonisation, particularly after the later enactment of Qanun Aceh No. 12 of 2025 amending Qanun Aceh No. 6 of 2014 and Law No. 20 of 2025 on the new Criminal Procedure Code. The contribution of the study lies in identifying a specific normative gap: the four-witness rule is expressly articulated for zina but not equivalently operationalised for liwāṭ, even though several juristic traditions analogise liwāṭ to zina through qiyās.